Removal of phosphate from aqueous solution by biochar derived from anaerobically digested sugar beet tailings - Yao, Ying; Gao, Bin; Inyang, Mandu; Zimmerman, Andrew R.; Cao, Xinde; Pullammanappallil, Pratap; Yang, Liuyan (Journal of hazardous materials, 2011)
Biochar converted from agricultural residues or other carbon-rich wastes may provide new methods and materials for environmental management, particularly with respect to carbon sequestration and contaminant remediation. In this study, laboratory experiments were conducted to investigate the removal of phosphate from aqueous solution by biochar derived from anaerobically digested sugar beet tailings (DSTC). Batch adsorption kinetic and equilibrium isotherm experiments and post-adsorption characterizations using SEM–EDS, XRD, and FTIR suggested that colloidal and nano-sized MgO (periclase) particles on the biochar surface were the main adsorption sites for aqueous phosphate. Batch adsorption experiments also showed that both initial solution pH and coexisting anions could affect the adsorption of phosphate onto the DSTC biochar. Of the mathematical models used to describe the adsorption kinetics of phosphate removal by the biochar, the Ritchie N_th-order ( N = 1.14) model showed the best fit. Two heterogeneous isotherm models (Freundlich and Langmuir–Freundlich) fitted the experimental isotherm of phosphate adsorption onto the biochar better than the Langmuir adsorption model. Our results suggest that biochar converted from anaerobically digested sugar beet tailings is a promising alternative adsorbent, which can be used to reclaim phosphate from water or reduce phosphate leaching from fertilized soils. In addition, there is no need to regenerate the exhausted biochar because the phosphate-laden biochar contains abundance of valuable nutrients, which may be used as a slow-release fertilizer to enhance soil fertility and to sequester carbon.